STRATEGI PEMBELAJARAN AKTIF SEPAK BOLA VERBAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 2 KAMPAR - Nurlini Eka Putri; Roza Linda; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research about application of active learning Football Verbal strategy to improve students learning achievement on the subject of hydrocarbon in class X SMAN 2 Kampar have been done. Tipe of research is experiment research with design randomized control group pretest-posttest. The sample consisted of two classes, which are X4 as experiment class and X3 as control class that randomly selected after testing normality and homogeneity. Experiment class was given treatment with implementing active learning Football Verbal strategy while the control class wasnot given active learning Football Verbal strategy. Analysis of data used t-test. Results of the analysis showed that tscore > ttable (3,66 > 1,67), it means that the active learning Football Verbal strategy can improve students achievement on the subject of hydrocarbon in class X SMAN2 Kampar. The category improvement of students learning achievement in experiment class was high category and in control class was medium category with N-gain 0,78 and 0,67 sequentially.Key Words : Active Learning Football Verbal strategy, Learning Achievement, Hydrocarbon